The Science base for Climate-Smart Agriculture in East Africa Webinar 28.08.14 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Climate-Smart Agriculture (CSA) offers a way to transform the world food system and achieve three goals: near-term productivity and food security; longer-term resilience and adaptation; and reductions in emissions across landscapes, agriculture and food systems. CCAFS has strived to address the knowledge needs for implementing and scaling up CSA. CCAFS provides a wide range of resources and tools, which can enable various stakeholders including farmers, governments, community organizations, and the private sector to implement CSA. This webinar aims to familiarize private sector stakeholders in East Africa to CCAFS resources and tools, ongoing work with key partners, and to encourage greater uptake. For more information about CCAFS activities in East Africa, see: https://ccafs.cgiar.org/regions/east-africa